Implementation of Religious Moderation in Madrasah Aliyah Arroja Garut Regency - Hasanah, Aan; Rohimah, Elis; Amirudin, Ja’far (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to describe the pattern of the spread of radicalism in madrasah using descriptive-qualitative research. The data used include two things, namely primary data and secondary data. Data collection techniques in the form are documentation, interviews, and observation. The results of this study indicate that radicalism enters madrasah through (1) classroom learning activities by teachers, (2) through textbooks that allegedly contain intolerance content, and (3) weak policies of principals/foundations in preventing the influence of radicalism. Meanwhile, the strategy offered is to make (1) the teacher a role model for cultivating tolerance and religious moderation for students and having an excellent national perspective. (2) Critical Learning. Engaging, creative, critical thinking, and student-centered learning practices. Teachers must design learning that inspires students' reasoning, essential learning (critical thinking & critical pedagogy), and problem-based learning. (3) Teacher Development, the Ministry of Religion has compiled a module designated for the development of teachers and education personnel in the madrasah environment.